PENYELESAIAN PENCEMARAN LINGKUNGAN HIDUP MELALUI PENDEKATAN BUDAYA HUKUM DAN HUBUNGAN KEMITRAAN ( SUATU STUDI KASUS ) - Dahlia, Agatha Jumiati & (Wacana Hukum, 2011)
Abstract  : Simple society likes villagers is mostly choose conflict finishing of live    environment by discussion to avoid the dispute which is in order to reach the substantial justice. Conflict finishing by discussion using partner relationship approachment which get involved three strength elements : government, industry world and society is a step to get ideal civil society. Keywords : live environment pollution, culture of law and partner relationship.